Imaging Pulmonary Gene Expression with Positron Emission Tomography - Richard, Jean-Cristophe; Zhou, Zhaohui; Ponde, Datta E; Dence, Carmen S; Factor, Philip; Reynolds, Paul N; Luker, Gary D; Sharma, Vijay; Ferkol, Tom; Piwnica-Worms, David; Schuster, Daniel P (American journal of respiratory and critical care medicine, 2003)
We evaluated positron emission tomographic imaging of pulmonary transgene expression, using an enhanced mutant herpes simplex virus-1 thymidine kinase as the reporter gene, in the lungs of normal rats. Sixteen rats were studied 3 days after an intratracheal administration of 5 x 10(9) to 1 x 10(11) viral particles of a replication-incompetent adenovirus containing a fusion gene of the mutant kinase and green fluorescent protein. Three rats infected with adenovirus containing no insert (null vector) served as control subjects. Images were obtained 1 hour after an intravenous injection of 9-(4-[18F]-fluoro-3-hydroxymethylbutyl)guanine, an imaging substrate for the viral kinase. After euthanasia, tissue radioactivity was determined in a gamma counter, and thymidine kinase activity and green fluorescent protein levels were measured in lung tissue samples. Imaging and gamma counting radioactivity measurements were strongly and linearly correlated (r2 = 0.96, p < 0.001). Imaging detected thymidine kinase expression above background (null vector) in 15 of 16 rats, even at low viral doses that produced little to no measurable green fluorescent protein expression. Lung 9-(4-[18F]-fluoro-3-hydroxymethylbutyl)guanine uptake (as assessed by imaging) correlated with in vitro assays of both kinase activity (r(2) = 0.48, p < 0.001) and fluorescent protein (r(2) = 0.46, p < 0.001). We conclude that positron emission tomographic imaging is a sensitive and quantitative method for detecting pulmonary reporter gene expression noninvasively.